X-ray powder diffraction data for 2-[((3R)-5-oxo-4-phenyltetrahy drofuran-3-yl)methyl]isoindoline-1, 3-dione, C19H15NO4. Issue 2 (1st April 2016) - Zheng, Shoujun; Xu, Kailin; Wang, Qing; Tang, XiaoLin; Huang, Yanmei; Tang, Pei Xiao; Chen, Lijuan; Li, Hui
Abstract : 2-[((3R)-5-oxo-4-phenyltetrahydrofuran-3-yl)methyl]isoindoline-1, 3-dione, C19 H15 NO4, was synthesized for the first time. Its structure was characterized by element analysis, ultraviolet spectrometry, nuclear magnetic resonance, and single X-ray diffraction (SXRD). X-ray powder diffraction (XRPD) data of title compound were collected and calculated. The result of SXRD shows that its crystal system is orthorhombic, space group is Pbca, and unit-cell parameters are a = 8.861 57(7), b = 14.6666(10), c = 24.4247(19) Å, α = β = γ =90°, unit-cell volume V = 3174.4 Å 3, and Z = 8. All XRPD measured lines were indexed and consistent with the Pbca space group [ a = 14.639(7), b = 24.378(3), c = 8.918(1) Å, α = β = γ = 90°, unit-cell volume V = 3182.7(9) Å 3, Z = 8]. No detectable impurities were observed.